Performance evaluation of vanets using wireshark - Ahmed, Shakeel; V.K. Ramesh, N (International Journal of Engineering and Technology, 2018)
Vehicular Adhoc Networks (VANETs) have become a hot area of research and development since few years. It is actually a subclass of Mobile Adhoc Networks (MANETs) where each node is a vehicle and when the nodes come in the communication range of each other, they form a network. In VANETs, Vehicle to Vehicle(V2V) and Vehicle to Infrastructure(V2I) communication takes place where nodes themselves acts as servers and /or clients for sharing & exchanging of information. VANETs find applications in road safety also have the potential to improve traffic efficiency and convenience by communicating with peer vehicles and roadside units. As the nodes move with high speed, the topology is dynamically varying and designing a routing protocol for such a dynamically varying network is a challenge. Also other challenges of VANETs are security, connectivity among vehicles, cross layer design issues, mobility & validation.In this paper, a VANET scenario is simulated using Wireshark Simulator in IEEE 802.16e (WiMAX) and IEEE 802.11p (WAVE) environment and the performance evaluation parameters like packet loss ratio and throughput. The simulation results are performed by scaling the network size using both the environments i.e., WiMax and WAVE and the results are evaluated by comparing throughput and packet loss ratio. WiMAX outperforms WAVE in a VANET environment in a big network